Edukasi pada Ibu tentang Pemantauan Tumbuh Kembang Anak - Tina Yuli Fatmawati; Ariyanto Ariyanto; Nel Efni; Asparian Asparian (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
The quality of the child is largely determined by the continuity of the process of growth and development from the period in the womb to the period at the beginning of his life. At the age of 0-6 years is a period of formation of the basics of human personality, thinking skills, skills, independence, socializing and intelligence. The role of parents, caregivers and teachers in monitoring a child's growth and development is very important, so that delays in the child's growth and development can be detected as early as possible. The aim of this community service is that parents are able to understand the growth and development of children. The service methods applied are lectures, discussions, mentoring. The service activity was carried out at the Selamat Village Kindergarten, with 20 parents of students participating. The results of community service were obtained, the results of the pre-test before education were 9 respondents (45%) who understood about child growth and development, the results of the post test were 19 respondents (95%) who understood about child growth and development. With this outreach, it is hoped that mothers will continue to increase their knowledge and be willing to practice monitoring their children's growth and development